2007
DOI: 10.1186/1471-2180-7-106
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics and signature proteins for the alpha Proteobacteria and its main groups

Abstract: Background: Alpha proteobacteria are one of the largest and most extensively studied groups within bacteria. However, for these bacteria as a whole and for all of its major subgroups (viz. Rhizobiales, Rhodobacterales, Rhodospirillales, Rickettsiales, Sphingomonadales and Caulobacterales), very few or no distinctive molecular or biochemical characteristics are known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
120
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(133 citation statements)
references
References 83 publications
13
120
0
Order By: Relevance
“…CGH profile analysis suggested that the absence of GIs on the genome types 122 and 6 in B. japonicum extends to non-Bj strains (Figure 1). So far, the GI sequences have proven specific for B. japonicum USDA110 by our BLAST search (http://www.ncbi.nlm.nih.gov/ blast) of data on the genomes of 10 strains of the family Bradyrhizobiaceae (Gupta and Mok, 2007), although we found partial homologous sequences within the GIs in Bradyrhizobium sp. BTAi1 and ORS278, R. palustris CGA009, BisA53, BisB18, BisB5 and HaA2, and Rhizobium leguminosarum bv.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…CGH profile analysis suggested that the absence of GIs on the genome types 122 and 6 in B. japonicum extends to non-Bj strains (Figure 1). So far, the GI sequences have proven specific for B. japonicum USDA110 by our BLAST search (http://www.ncbi.nlm.nih.gov/ blast) of data on the genomes of 10 strains of the family Bradyrhizobiaceae (Gupta and Mok, 2007), although we found partial homologous sequences within the GIs in Bradyrhizobium sp. BTAi1 and ORS278, R. palustris CGA009, BisA53, BisB18, BisB5 and HaA2, and Rhizobium leguminosarum bv.…”
Section: Discussionmentioning
confidence: 53%
“…Bradyrhizobium japonicum is a member of the family Bradyrhizobiaceae, which belongs to the order Rhizobiales in the Alphaproteobacteria (Gupta and Mok, 2007). Members of Bradyrhizobiaceae include a number of nonsymbiotic bacteria with diverse biochemical functions such as photosynthesis (Molouba et al, 1999;Larimer et al, 2004;Giraud et al, 2007), oligotrophy (Saito et al, 1998;King, 2007), 2,4-dichlorophenoxyacetic acid degradation (Kamagata et al, 1997) and nitrification (Starkenburg et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a bacterial population related to rhizobia may be passively affected by a part of the autoregulation systems for regulating rhizobia. In fact, the three genera (Aurantimonas, Methylobacterium and Rhizobium) in Rhizobiales found in the present study are all closely related to Bradyrhizobium spp., endosymbionts of soybeans (Gupta and Mok, 2007). Another surprising finding was the high similarity observed for the population shifts of Alpha-and Gammaproteobacteria between two different environmental factors: the effects of genotypes under SN fertilization and the effects of the nitrogen fertilization under the HN fertilization condition.…”
Section: Discussionmentioning
confidence: 92%
“…The proteins that were of interest generally involved a large increase in the expected values (E-values) from the last hit for the cluster I clostridia to the first hit from any other organism. Further, the E-values of these latter hits were generally greater than 10 23 , which indicates a weak level of similarity that can occur by chance (Gao et al, 2006;Gupta, 2006;Gupta & Mok, 2007). All promising proteins were further analysed using the PSI-BLAST program (Schaffer et al, 2001) to confirm their group specificity.…”
Section: R S Gupta and B Gao 286mentioning
confidence: 99%
“…Alphaproteobacteria, Epsilonproteobacteria, Chlamydia, Actinobacteria, Cyanobacteria, Deinococcus-Thermus, Bacteroidetes, etc. ; Griffiths et al, 2006;Gao et al, 2006;Gupta, 2006;Gupta & Lorenzini, 2007;Gupta & Mok, 2007). These newly discovered molecular markers provide valuable tools for biochemical, diagnostic, taxonomic and evolutionary studies on these bacteria (Koonin & Galperin, 1997;Binnewies et al, 2006).…”
Section: Introductionmentioning
confidence: 99%